丹戎布拉大学师范教育学院汉语专业2017届学生的比较句 “没有“和“不比”掌握情况分析 - Stefani Brigita; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractComparative Chinese sentences refer to sentences that contain comparative words. Comparative sentences are also used to compare differences in the characters and degrees of different people or objects. Comparative Chinese sentences contain positive and negative sentences. Comparative sentences consisting of “bi” usually appear in the positive form, and if negative, often use the “bu” form. However, although the word “bu” could be added before the word “比” to negate, the usage and meaning of “meiyou” were different. Negative comparative sentences in Mandarin are grammar that is difficult to master, which get students often to have mistakes, mixed use, and misuse.In order to find out how the students of Tanjung Pura University in the Chinese language study program class of 2017 have mastered the comparison sentence “meiyou” and “bubi”, the authors conducted a test to analyze student knowledge and find out the difficulties. This article uses a test method to investigate students’ mastery and analyze the difficulty of comparisons of Chinese sentences. From the results of this study the authors concluded that the correct level of students who used the comparison sentence “meiyou” reached 51.8%, the correct students who used the comparative sentence “bubi” reached: 46.8%. The difficulty of students in using Chinese comparative sentences for comparison sentences “meiyou” is in the using for “negating actions or things that have happened or happened before”; and the difficulty in “bubi” is not knowing the use of “words to praise” and “words to patronize.” Therefore, the authors hope that this research can improve students’ ability to use comparative sentences of “meiyou” and “bubi” in Mandarin.KeyWords: Comparative Chinese sentences, Meiyou And Bubi, An analysis of students mastery in using